Tracing Bugis ethnicity through the existence of yellow-crested cockatoo in Masakambing Island, Indonesia - Ihsannudin, Ihsannudin; Sriyono, Sriyono; Hasan, Fuad (ETNOSIA : Jurnal Etnografi Indonesia, 2022)
Masakambing Island has administratively located in the District of Masalembu, Sumenep Regency, East Java province, Indonesia. This island is an endemic habitat for the yellow-crested cockatoo sub-species abbotti (Cacatua sulphurea abbotti). This research aims to discover the history of the people inhabiting Masakambing island and traces of  Bugis culture through the existence of the yellow-crested cockatoo. The study was conducted using a qualitative method with an ethnographic design. The study results show that the origin people who inhabited this island were from the Bugis ethnic group. The local name Beka' reflects how the yellow-crested cockatoo is very close to Bugis culture on Masakambing island. Besides, the Bugis ethnic who inhabit Sulawesi island is familiar with the yellow-crested cockatoo, sub-species sulphurea, and djampea. The existence of yellow-crested cockatoos on Masakambing island still triggers questions because the location of Masakambing island is outside the Wallace line, which is not common to find families of parrots such as yellow-crested cockatoos.